Vitamin D in the Breast Cancer Continuum: A Systematic Review and Meta-Analysis of Primary Prevention, Patient Prognosis, and Adjunctive Treatment Response - Felix Setiawan; Yan Wisnu Prajoko; Niken Puruhita; Aliva Nabila Farinisa (HM Publisher, 2026)
Background: The role of vitamin D across the breast cancer spectrum remains complex and contested. Compelling preclinical antineoplastic mechanisms contrast with inconsistent clinical findings. Large randomized controlled trials (RCTs) show null effects for primary prevention, while observational studies often link higher vitamin D status at diagnosis with better prognosis. Key conflicts include this prevention-prognosis disconnect, debates over linear versus J-shaped prognostic dose-responses, and a